Pengaruh Customer Review dan Influencer Review terhadap Purchase Intention pada Wisata Umbul Kemanten - Devayanti Arnantika; Soepatini (Jurnal Manajemen Dirgantara, 2024)
The growing internet technology makes it easier to promote or introduce a product such as through social media with the aim of increasing consumer purchase intention. In this digital era, consumers often look at other customer reviews or reviews from an influencer before making a purchase decision. These reviews are considered important and also useful. By using trust as a moderating variable, this study examines the effect of customer reviews and influencer reviews on purchase intention on Umbul Kemanten tours. This research is quantitative research. The population in this reseacrh were residents of Greater Solo with a sample of 221 respondents were selected through the use of non-probability sampling methodology with purposive sampling type. Using the SmartPLS version 3.0 program, the partial least square (PLS) approach of the structural equation model (SEM) was applied to analyze the data in this study. The data analysis technique goes through several stages, namely validity test, reliability test, R-square test, predictive relevance test (Q2), model fit test and hypothesis testing. The findings of this study indicate that customer and influencer reviews have no impact on purchase intention. The trust variable moderates the effect of customer reviews and influencer reviews on purchase intention on Umbul Kemanten tours and has a positive direct effect.